Rancang Bangun Media Pembelajaran Quiz Edukatif Bahasa Arab Berbasis Web di TPQ Athoyyibin Kabupaten Wakatobi - Shinta Esabella; Muh NurHidayatullah; Farida Idifitriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This research aims to design and develop a web-based Arabic educational quiz media that integrates gamification elements (points, levels, badges, and leaderboards) to create a more interactive and engaging learning experience. The research method uses qualitative and quantitative approaches with data collection through observation, interviews, and literature study. Software development is carried out using the Software Development Life Cycle (SDLC) Agile model. The application is built using the Laravel framework (PHP), MySQL database, and Tailwind CSS and Alpine.js for the user interface. System functionality testing is conducted using the User Acceptance Testing (UAT) method involving 17 respondents consisting of 3 admins, 4 teachers, and 10 students. The results show that the web-based Arabic educational quiz media Quiz was successfully developed with three user levels (admin, teacher, and student) and gamification features that increase student engagement and learning motivation. UAT results show an overall acceptance rate of 4.40 out of a scale of 5 (Good category), with students giving the highest rating of 4.76 (Very Good), especially in the motivation and learning aspect which obtained a Score of 4.80. This application is expected to be an alternative solution in supporting more effective and attractive Arabic language learning at TPQ Athoyyibin.